The subfunctionalization of shox and shox2 paralogs in shark highlights both shared and distinct developmental mechanisms of branchial arches and fins - Ermakova, Galina V.; Meyntser, Irina V.; Lyubetsky, Vassily A.; Zaraisky, Andrey G.; Bayramov, Andrey V. (Frontiers in Cell and Developmental Biology, 2025)
The genomes of most gnathostomes contain two paralogs of the shox gene, shox and shox2, both of which are implicated in the development of two key morphological innovations: the jaw apparatus derived from the branchial arches and the paired appendages, whose evolutionary origins remain debated. Here, we investigate the expression patterns of shox and shox2 paralogs in the gray bamboo shark (Chiloscyllium griseum), a representative of Chondrichthyes, a basally divergent gnathostome lineage. The paired fins of cartilaginous fishes are considered a basal model for gnathostome appendages. Our findings suggest spatial subfunctionalization of the shox and shox2 genes. Specifically, shox is expressed in the mandibular and branchial arches, as well as in paired and unpaired fins, indicating shared developmental mechanisms among these structures. In contrast, shox2 expression is predominantly restricted to paired fins, highlighting distinct developmental features that differentiate them from the evolutionarily older median fins.